Analisis Intensitas Cahaya Lampu Pijar dengan Menerapkan Metode Gray Level Co-occurence Matrik - Elvianto Dwi Hartono; Bagus Hardiansyah (STMIK Budi Darma, 2022)
This paper proposes primary dataset with 13 images thermal capture, 8 high frequency and 4 low frequency. We utilize thermal images fluorescent lamp and using image processing with extraction feature GLCM method. Furthermore, Contrast, Correlation. Energy, Homogeinity dan sudut 0°, 45°, 90°, 135°, these feature texture using for calculated validation compare with both exsperiment qualitative results in Table1 and Table2. Therefore, exsperiment with fluorescent lamp Figure 2 quantitative results significant in Table1. Quantitative results with fluorescent lamp in Table2 extraction feature GLCM method with angle 0°, 45°, 90°, 135° and in Table1 quantitaive result with low frequency 50 Hz with T (oC) 50 is significantly robust. Comparable quantitative results in Table2 with low frequency 50 Hz from extraction feature mean value angle 0°, 45°, 90°, 135° Contrast (0.0363), Correlation (0.9959), Energy (0.1353), and Homogeneity (0.9832).